Aging engineers’ occupational self-efficacy—a mixed methods study - Wallin, Stina; Fjellman-Wiklund, Anncristine; Fagerström, Lisbeth (Frontiers in Psychology, 2023)
Introduction Engineers’ work has become more complex with increased demands in today’s continuously changing working life. Self-efficacy is essential for successfully meeting work related changes and coping with the negative effects of job demands among engineers. However, less is known about ageing workers’ occupational self-efficacy. Therefore, this study explores what positively and negatively affected ageing engineers’ occupational self-efficacy beliefs that they can continue working until expected retirement age, and to what extent emerged categories occurred. Methods The study design was exploratory, using mixed methods with a qualitative to quantitative approach. A total of 125 engineers, aged between 45-65 years, answered two open-ended survey questions about what positively and negatively affect their occupational self-efficacy beliefs to continue working. First, data was analyzed using manifest qualitative content analysis. Next, descriptive statistics were performed based on the results of the qualitative study. Results The analyses revealed that, besides competence development, and supportive leadership and colleagues, the engineers’ own health and work environmental aspects must be addressed to enhance their self-efficacy to continue working. Intrinsic motivation and positive life orientation were emphasized, as were personal life and economy. Discussion The ageing engineers’ own health seems to be prominent in their self-efficacy regarding a full working life; consequently, support still needs to address issues affecting health.